MODAL SOSIO-POLITIK KEMENANGAN CALEG PEREMPUAN PADA PEMILU 2024 (Studi Kasus atas Terpilihnya Maria Roswita Mea Laki di Dapil III Nagekeo) - Febronius Yano; Didimus Dedi Dhosa; Yohana Fransiska Medho (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research is titled The Socio-Political Capital Behind the Victory of Female Legislative Candidates in the 2024 Election: A Case Study of Maria Roswita Mea Laki’s Election in Electoral District III, Nagekeo.